2017
DOI: 10.3892/etm.2017.5392
|View full text |Cite
|
Sign up to set email alerts
|

miR-144 inhibits growth and metastasis of cervical cancer cells by targeting VEGFA and VEGFC

Abstract: Abstract. MicroRNAs (miRs) are aberrantly expressed in various cancer types and have critical roles in their genesis and progression. miR-144 has been identified to be involved in the development of hepatocellular carcinoma and rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…In contrast, miR‐144 is aberrantly downregulated and acts as a tumour suppressor in several types of tumours, such as hepatocellular carcinoma (He et al., ), gastric cancer (Liu et al., ) and breast cancer (Yin, Cai, Meng, Sui, & Jiang, ). Interestingly, miR‐144 was reported to be significantly downregulated in cervical cancer tissues and cell lines, and overexpression of miR‐144 could inhibit cell proliferation and invasion in cervical cancer cells (Tao et al., ). In our study, a dual luciferase reporter assay demonstrated that miR‐144 repressed the expression of ITGA6 by directly targeting to its 3′‐UTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, miR‐144 is aberrantly downregulated and acts as a tumour suppressor in several types of tumours, such as hepatocellular carcinoma (He et al., ), gastric cancer (Liu et al., ) and breast cancer (Yin, Cai, Meng, Sui, & Jiang, ). Interestingly, miR‐144 was reported to be significantly downregulated in cervical cancer tissues and cell lines, and overexpression of miR‐144 could inhibit cell proliferation and invasion in cervical cancer cells (Tao et al., ). In our study, a dual luciferase reporter assay demonstrated that miR‐144 repressed the expression of ITGA6 by directly targeting to its 3′‐UTR.…”
Section: Discussionmentioning
confidence: 99%
“…As a class of endogenous non-coding small RNAs with 21-23 nucleotides, miRNAs, have been shown to regulate posttranscriptional eukaryotic gene expression effectively (Yang et al, 2015). Among these miRNAs, miR-144 was found to be significantly downregulated in cervical cancer tissues, and ectopic expression of miR-144 could inhibit cervical cancer cell migration and invasion by targeting vascular endothelial growth factor A (VEGFA) and VEGFC (Tao et al, 2018). Integrin 6 (ITGA6) is a vital transmembrane protein and acts as an oncogene in various cancers (Raab-Westphal, Marshall, & Goodman, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-144 is significantly decreased in CC cells when compared to normal cervical cells. MiR-144 suppresses the proliferation and angiogenesis of tumor cells by targeting VEGFA and VEGFC [109]. Furthermore, miR-144 overcomes resistance to cisplatin (CDDP) through targeting of LIM homeobox 2 (Lhx2), leading to apoptosis and inhibiting invasion in tumor cells [110].…”
Section: Mir-144 In Cervical Cancermentioning
confidence: 99%
“…Cancer cells overexpress COX-2 and prostaglandins that reduce cancer cell apoptosis and induce angiogenesis via VEGF (Fosslien, 2001b). Recently, miR-144 acts as a tumor suppressor in the proliferation and metastasis of cervical cancer cells by directly targeting VEGF (Tao et al, 2018). The present study identified with qPCR and western blot analyses that the downregulation of miR-144 may contribute to COX-2 and VEGF expression in ovarian cancers.…”
Section: Discussionmentioning
confidence: 58%